2017
DOI: 10.1259/bjr.20160596
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric characterization and behaviour in small X-ray fields of a microchamber and a plastic scintillator detector

Abstract: Objective: The aim of this work was to investigate the main dosimetric characteristics and the performance of an A26 Exradin ionization microchamber (A26 IC) and a W1 Exradin plastic scintillation detector (W1 PSD) in small photon beam dosimetry for treatment planning system commissioning and quality assurance programme. Methods: Detector characterization measurements (short-term stability, dose linearity, angular dependence and energy dependence) were performed in water for field sizes up to 10 3 10 cm 2 . Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…The CLR factors for the W1 and W2 detector were determined at 22 C, which represents clinical measurements conditions. Our results take into account the CLR correction, which shows a linearly decreasing temperature response of the Exradin W2 and W1 detectors, which are in good agreement with Wooton et al and Carrasco et al 32 Pasquino et al 20 reported negligible field output factor variations due to irradiation geometries (parallel vs perpendicular) for different fields sizes (ranging from 0:6 Â 0:6 cm 2 to 10 Â 10 cm 2 at 10 cm depth) using the W1 Exradin scintillator. Our results show that the field output factor variations are within 3% for the 0:5 Â 0:5 cm 2 field size and 1% for the 1 Â 1 cm 2 and larger field sizes.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The CLR factors for the W1 and W2 detector were determined at 22 C, which represents clinical measurements conditions. Our results take into account the CLR correction, which shows a linearly decreasing temperature response of the Exradin W2 and W1 detectors, which are in good agreement with Wooton et al and Carrasco et al 32 Pasquino et al 20 reported negligible field output factor variations due to irradiation geometries (parallel vs perpendicular) for different fields sizes (ranging from 0:6 Â 0:6 cm 2 to 10 Â 10 cm 2 at 10 cm depth) using the W1 Exradin scintillator. Our results show that the field output factor variations are within 3% for the 0:5 Â 0:5 cm 2 field size and 1% for the 1 Â 1 cm 2 and larger field sizes.…”
Section: Discussionsupporting
confidence: 91%
“…Pasquino et al . reported negligible field output factor variations due to irradiation geometries (parallel vs perpendicular) for different fields sizes (ranging from 0.6×0.6cm2 to 10×10cm2 at 10 cm depth) using the W1 Exradin scintillator.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations